Penggunaan Wabosang Sebagai Media Pendidikan Seksual Pada Anak-Anak Bantaran Sungai Jembatan Merah Surabaya - Naili Sa'ida; Aristiana Prihatining Rahayu (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
This study aims to describe the use of wabosang media as sexual education in early childhood. This research was conducted in Bantaran Sungai Jembatan Merah Kota Surabaya. This research used descriptive qualitative research method with case study type. Data collection uses observation, interviews, and documentation. Data obtained then analyzed using interactive model proposed by Miles and Huberman. From this research it is known that sexual education can be done through media (WaBoSang). The use of wabosang media as sexual education, the child is able to know the correct way of dressing, the child knows the parts of the body that must be closed, the child is able to know only the mother and himself who can touch the covered body parts, the child is also able to know what must be done when there are people who act evil.